Pengaruh Lingkungan Belajar terhadap Tingkat Stres Mahasiswa Awal dan Mahasiswa Akhir - Titan Agestin; Salsa Ardhya Putri; Tio Indra Gunawan; Yadi Ruyadi; Intan Indah Megasari (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to analyze the influence of the learning environment on students’ stress levels by comparing the experiences of first-year and final-year students in facing academic demands. The background of this research highlights the high prevalence of academic stress among university students, often triggered by physical, social, and academic factors. A qualitative approach was employed through in-depth interviews with four students (two first-year and two final-year) and a psychologist as an expert informant. The findings reveal that first-year students are more vulnerable to adaptation stress caused by uncomfortable classroom conditions, ineffective online learning methods, and organizational activities, while final-year students experience completion stress related to thesis preparation, heavy workloads, and limited campus facilities. The study emphasizes that a supportive learning environment, adequate facilities, and positive academic communication can help students manage stress more adaptively. Practical recommendations include improving campus infrastructure, strengthening social support, and developing academic policies that are responsive to students’ psychological needs at different stages of study.